Operations research and quantitative economics : an elementary introduction - Theil, Henri; Boot, Johannes Cornelius Gerardus; Kloeck, Teun (New York, McGraw-Hill Book Co., 1965)
The purpose of this book is to present a survey of the methods and accomplishments of econometrics and operations research at a nontechnical level.
Translation of Voorspellen en beslissen.
Includes bibliographies.
occ 17/01/2019, ijb 06/03/2019
Loans
Keywords: Operations research; Quantitative economics